Alpha1-antitrypsin deficiency and asthma. Issue 1 (February 2021) - Pini, Laura; Paoletti, Giovanni; Heffler, Enrico; Tantucci, Claudio; Puggioni, Francesca
Abstract : Purpose of review: The aim of the article is to highlight the association between α1-antitrypsin deficiency (AATD) and asthma. Recent findings: AATD is one of the most common and underrecognized autosomal disorders associated with an increased risk of developing liver and lung diseases. An association between α1-antitrypsin and asthma has been suggested, especially with severe forms of this disease. Many studies have shown an increased prevalence of asthma in the α1-antitrypsin-deficient population overtime (4–38%). The biological mechanism underlying these two conditions and able to bind them has not yet been well investigated. As α1-antitrypsin is the main inhibitor of the serine proteinase and it is an important anti-inflammatory protein with pronounced immunomodulatory activities, it can be hypothesized that the link between AATD and asthma might be represented by the elastase/antielastase imbalance and the proinflammatory effect that occurs because of the reduction of this protein. Summary: There is a strong need for further researches to better understand the molecular mechanisms binding AATD and asthma. It is also recommendable to screen for AATD, late-onset asthma patients, and/or those with not fully reversible airways obstruction.